Ontology-based conceptual model for quality assurance in higher education - Ali, Sedig Ahmed Babikir (2019)
Quality in higher education is a complex, controversial and continuously evolving area of research. The concept of quality assurance (QA) emerged and is widely used nowadays within a range of processes of managing quality in higher education. A review of a number of existing standards of QA revealed many research gaps such as structure variations, lack of shared knowledge and understanding, lack of standardized use of terminology and the lack of practical and semantic support and guidelines on developing conceptual models of quality assurance in higher education. The Design Science (DS) approach in Information Systems discipline provides clear guidelines for designing, developing, demonstrating and evaluating novel solutions for defined problems with the aim of extending the boundaries of human and organizational capabilities by producing new, advanced and original artifacts. Therefore, to address the highlighted gaps, this research adopts the design science research methodology (DSRM) provided by Peffers (2008) comprising a sequence of six activities: (1) Problem Identification and Motivation, (2) Definition of the Objectives of a Solution, (3) Design and Development, (4) Demonstration, (5) Evaluation, and (6) Communication. This thesis demonstrates the applicability and usefulness of domain models with the phenomenon of quality in the higher education domain to support shared understanding, communication, and domain learning and problem-solving by introducing a universal approach to the domain of quality assurance. The ontology-based conceptual model for quality assurance (OntoQA), which is the main artifact delivered by this research, has been developed to faithfully capture the domain of quality assurance of academic programmes. OntoQA covers its domain to the extent required by intended usage, providing a reference ontology to facilitate design, development, monitoring, evaluation and improvement of quality academic programmes, and to assist in designing quality assurance systems. This research has introduced OntoQA as a new approach to designing, developing, monitoring and evaluating quality academic programmes, as well as the design and development of quality assurance systems. Quality assurance in higher education is a community-based process which requires consensus between stakeholders, therefore, OntoQA enhances communications, and facilitates streamlined collaboration on joint goals. Using OntoQA and getting familiar with the idea of conceptualising quality assurance in higher education facilitates tool developers, which would potentially help higher education providers to integrate quality when designing new programmes, or while reviewing and improving existing ones in conformance with international standards.